A tale of two transitions: Mobility dynamics in the People's Republic of China and Russia after central planning - Kristina Butaeva; Lian Chen; Steven N. Durlauf; Albert Park (Asian Development Bank (ADB), 2025)
This paper examines intergenerational mobility in the People's Republic of China (PRC) and Russia during their transitions from central planning to market systems. We consider mobility as movement captured by changes in status between parents and children. We provide estimates of overall mobility, which involves mobility during transition to a system's steady state, as well as steady state mobility, which captures long-run mobility independent of transitional dynamics or shifts in the marginal distribution of outcomes across generations. We further decompose overall mobility into structural and exchange components. We find that the PRC exhibits more overall educational mobility than Russia, mostly because of greater structural mobility, whereas Russia exhibits greater steady-state educational mobility. In contrast, both overall and steady state occupational mobility are similar in the PRC and Russia. Comparing these results to the United States (US), we find steady state mobility in education is substantially higher in the US and Russia compared to the PRC, but occupational steady state mobility is comparable in all three countries.
Keywords: J62; I25; P36; 330; intergenerational mobility; education; occupation; transition economy